Elevated atmospheric CO2 concentration increases rice blast severity - Gória, Marina Meloni [UNESP]; Ghini, Raquel [UNESP]; Bettiol, Wagner [UNESP] (FapUNIFESP (SciELO), 2013)
The predicted atmospheric carbon dioxide concentration's increases are likely to alter plant-pathogen interactions. To assess the effects on rice blast, during three years (2007, 2008 and 2009), three rice cultivars (Agulha Precoce, Shao Tiao Tsao and Caloro) were exposed to elevated CO2 air concentration (approximately 100 - 300 μmol mol-1 higher than ambient) in open-top chamber facility. The disease was more severe under high CO2 concentration. Area under disease progress curve was 35.43 under high CO2 concentration and 17.48 for the current concentration. Leaves of treated plants tended to contain less silicon. In 2009, plant height of two cultivars was greater in high CO2. Understanding and predicting the climate-driven changes in the agroecosystem may allow the development of adaptation strategies in order to minimize crop losses. © Springer-Verlag Berlin Heidelberg 2011.
Keywords: Carbon dioxide; Climate change; Magnaporthe oryzae; Oryza sativa; Pyricularia oryzae